Vacancy-rich Ru / RuSex heterostructure electrocatalyst as well as preparation method and application thereof

The preparation of vacancy-rich Ru/RuSe heterostructure electrocatalysts through Joule heating technology, which solves the problem of low activity and poor stability of Ru-based catalysts in alkaline and seawater environments, and achieves efficient hydrogen evolution reaction performance and long-term stability, and is suitable for large-scale electrolyzed seawater hydrogen production.

CN120465054AActive Publication Date: 2025-08-12GUANGXI UNIV

Patent Information

Application Number
CN202510983271.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-08-12
Estimated Expiration
2045-07-17

AI Technical Summary

Technical Problem

The existing Ru-based electrocatalysts have low catalytic activity and poor stability in alkaline and seawater environments, and the traditional preparation process is complex and difficult to accurately regulate the catalytic performance.

Method used

The vacancies-rich Ru/RuSe heterostructure electrocatalyst was prepared by using Joule heating technology. The RuSe2 powder was synthesized by hydrothermal method and then heated in an inert or reducing atmosphere to form a heterostructure of a cubic RuSe2 matrix with selenium-rich vacancies and metal Ru nanoparticles.

Benefits of technology

The catalytic activity and stability have been significantly improved. The Ru/RuSe heterostructure has an overpotential of only 21 mV at a current density of 10 mA·cm-2 in alkaline water and 26 mV in alkaline seawater. It is stable at a current density of 800 mA·cm-2 for 400 hours, and its performance is better than that of commercial Pt/C catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120465054A_ABST
    Figure CN120465054A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy nano material technology and water electrolysis hydrogen production, and particularly relates to a vacancy-rich Ru / RuSex heterostructure electrocatalyst as well as a preparation method and application of the vacancy-rich Ru / RuSex heterostructure electrocatalyst. The electrocatalyst is composed of a cubic phase RuSe2 matrix rich in selenium vacancy and metal Ru nano-particles which are uniformly distributed and stably anchored on the surface of RuSe2. The preparation method comprises the following steps: synthesizing precursor RuSe2 powder by a hydrothermal method, and carrying out Joule heating treatment on the RuSe2 powder in an inert atmosphere or a reducing atmosphere environment to obtain the vacancy-rich Ru / RuSex heterostructure electrocatalyst. The catalyst disclosed by the invention shows excellent hydrogen evolution performance under alkaline water and alkaline seawater conditions, and overpotentials of only 21 mV and 26 mV under the current density of 10 mA. Cm <-2 > are respectively realized; and the battery can stably run for 400 hours under the current density of 800mA. Cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy nanomaterial technology and water electrolysis hydrogen production, and specifically relates to a vacancy-rich Ru / RuSe x Heterostructured electrocatalysts, preparation methods, and applications thereof. Background Art

[0002] With the rapid development of clean energy technologies, hydrogen production by water electrolysis has become an important path to achieve large-scale application of hydrogen energy due to its zero-carbon emissions, high purity, and renewable energy-driven advantages. The key to improving electrolysis efficiency lies in the development of high-performance electrocatalysts. The precious metal platinum (Pt) has long been considered an ideal catalyst for the hydrogen evolution reaction (HER) due to its hydrogen adsorption free energy close to the thermodynamic optimum. However, the scarcity and high price of platinum resources have severely restricted its large-scale industrial application. Ruthenium (Ru), as a relatively abundant non-platinum precious metal with excellent electrocatalytic properties, has attracted widespread attention. However, the negative hydrogen adsorption free energy of metallic Ru leads to excessive adsorption of hydrogen intermediates, hindered hydrogen release, and limited its HER catalytic performance, especially in complex electrolysis environments such as alkaline or seawater.

[0003] To overcome the drawbacks of Ru's hydrogen adsorption, researchers have proposed constructing Ru-based compounds based on it. Among them, ruthenium selenide (RuSe2) has attracted widespread attention in hydrogen evolution electrocatalysis due to its stable crystal structure, moderate band gap, and tunable electronic structure. The introduction of Se elements can adjust the d-orbital electronic state distribution of Ru, improve its hydrogen adsorption behavior, and enhance reaction activity. However, RuSe2 itself has poor conductivity, limited electron transport, and limited exposure of its catalytic active sites, making it difficult to achieve efficient HER catalysis alone. In order to further improve the catalytic performance, it is urgent to enhance performance through structural design, such as constructing heterogeneous interfaces and regulating defect structures.

[0004] Existing synthesis methods for ruthenium-based catalysts and their heterogeneous structures mostly rely on traditional heat treatment processes such as high-temperature calcination, hydrothermal reaction, and atmosphere reduction. These methods usually have problems such as high energy consumption, long reaction time, and imprecise structural control. It is difficult to achieve precise control of interface morphology and vacancy defects, which affects the stability of catalytic performance and industrial scale-up application.

[0005] In recent years, Joule heating, an emerging method for rapid material synthesis, has garnered attention in the field of electrocatalytic material preparation due to its advantages, including rapid heating rates, low energy consumption, and strong localized thermal effects. This technique involves applying an electric current directly to a conductive precursor, achieving rapid heating and simultaneously creating a localized reducing environment within the material, which facilitates the reduction of metal ions and the formation of vacancy defects. This provides a new synthetic pathway for constructing structurally optimized, defect-controllable Ru-based catalytic materials. Summary of the Invention

[0006] The purpose of the present invention is to solve the problems of low activity, poor stability and complex preparation process that are difficult to accurately control in existing alkaline water / alkaline seawater Ru-based hydrogen evolution catalysts, and to provide a vacancy-rich heterostructure electrocatalyst with a simple preparation method, high catalytic activity, strong stability and suitability for long-term operation at high current density.

[0007] Specifically, the present invention provides a vacancy-rich Ru / RuSe x Heterogeneous structure electrocatalyst, the catalyst is composed of a cubic RuSe2 matrix rich in selenium vacancies and metal Ru nanoparticles uniformly distributed and stably anchored on the surface of RuSe2; the cubic RuSe2 matrix rich in selenium vacancies belongs to Pa3 - The invention relates to a cubic crystal system of a space group, wherein Ru atoms are located in a face-centered cubic lattice, and Se atoms form Se2 pairs and fill the octahedral interstitial sites in the crystal system to form a stable Ru-Se coordination structure; the selenium vacancies are uniformly distributed in the matrix and are preferentially enriched along high-energy crystal planes; a clear heterogeneous interface exists between the metal Ru nanoparticles anchored on the RuSe2 surface and the matrix, and the particles are tightly anchored by bonding.

[0008] The heterostructure effectively optimizes the electronic structure and hydrogen adsorption energy by regulating the interface between selenium vacancies and metal Ru, significantly improving the catalytic activity and long-term stability of the hydrogen evolution reaction.

[0009] The average size of the catalyst is 30-80 nm, and the average size of the metal Ru nanoparticles is 2-8 nm.

[0010] The present invention also provides a vacancy-rich Ru / RuSe x A method for preparing a heterogeneous structure electrocatalyst, the method comprising the following steps: The precursor RuSe2 powder is synthesized by hydrothermal method, and then the RuSe2 powder is subjected to Joule heating in an inert atmosphere or a reducing atmosphere to obtain vacancy-rich Ru / RuSe x Heterostructured electrocatalysts.

[0011] Specifically, the hydrothermal method for synthesizing the precursor RuSe2 powder specifically includes the following steps: (1) Disperse RuCl3·3H2O in deionized water, add disodium ethylenediaminetetraacetic acid and stir for 0.5-2 hours to prepare complex solution A; (2) Dissolve Se powder in concentrated KOH aqueous solution to prepare solution B; (3) Complex solution A is slowly added dropwise to solution B and mixed evenly, then transferred to a high-pressure reactor for hydrothermal reaction at 140-200°C for 8-36 hours. After cooling, the mixture is centrifuged until the pH is neutral and dried to obtain RuSe2 powder.

[0012] Preferably, the inert atmosphere is one of argon, nitrogen and helium, and the reducing atmosphere is one of argon containing hydrogen, nitrogen containing hydrogen and helium containing hydrogen.

[0013] Preferably, the Joule heating is performed using a constant current of 25 to 60 A, a heating temperature of 380 to 600° C., and maintained for 15 to 120 seconds.

[0014] Preferably, the Joule heating is performed with a constant current of 43-48 A, and the heating temperature is preferably 550-600°C.

[0015] Preferably, the molar ratio of RuCl3·3H2O, disodium EDTA, and Se is 1:(1.2-2):(1.5-3).

[0016] Preferably, the concentration of RuCl3·3H2O is 0.05-0.3 g / mL, and the concentration of KOH is 15-20 M.

[0017] The present invention also provides a vacancy-rich Ru / RuSe x Application of heterogeneous structure electrocatalysts, applying catalysts to hydrogen production by electrolysis of seawater.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Heterostructured Ru / RuSe Electrocatalyst of the Present Invention x The Ru nanoparticles have a hydrogen adsorption free energy close to zero, and have Se vacancies and regulate the d-band center of RuSe2, which enhances the water dissociation activity. The heterogeneous interface structure promotes electron transport, achieving a high-energy-density ionization at 10 mA·cm -2 The overpotential is only 21 mV in alkaline water and 26 mV in alkaline seawater at the current density, which outperforms most reported Ru-based catalysts and commercial 20% Pt / C catalysts. 2. The catalyst prepared by the present invention can be used in a self-assembled electrolytic cell at 800 mA·cm -2 The cell voltage remained unchanged for over 400 hours at a current density of 100 nm, demonstrating excellent industrial application prospects and the potential for large-scale hydrogen production from seawater electrolysis. 3. The preparation method of the present invention uses Joule heating to enhance the crystallinity of the material while simultaneously inducing in-situ reduction of Ru and generation of Se vacancies. This not only avoids the long heating time, high energy consumption, complex process, and nanoparticle agglomeration associated with traditional high-temperature reducing atmosphere calcination, but also allows for rapid control of defect concentration. 4. The preparation method of the present invention not only achieves the in situ reduction and loading of metallic Ru nanoparticles, but also induces the generation of Se vacancies, effectively improving the material's conductivity, active site density, and interfacial stability, regulating the material's electronic structure, enhancing water dissociation, and optimizing the hydrogen adsorption free energy. It exhibits excellent performance and long-term stability in the hydrogen evolution reaction of alkaline water and seawater. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 :(a) is the Ru / RuSe prepared in Example 1 x -43 catalyst is a scanning electron microscope (SEM) image, and (b) is a calculated average particle size of the catalyst.

[0020] Figure 2 :(a) is the Ru / RuSe prepared in Example 1 x (a) Transmission electron microscopy (TEM) image of the -43 catalyst, (b) is the average particle size calculation diagram of metal Ru nanoparticles.

[0021] Figure 3 : Ru / RuSe prepared in Example 1 x Electron paramagnetic resonance (EPR) spectra of RuSe2 prepared in -43 catalyst and comparative example 1.

[0022] Figure 4 : Ru / RuSe prepared in Examples 1 to 4 x -33.Ru / RuSe x -38、Ru / RuSe x -43.Ru / RuSe x -48 catalyst and the X-ray diffraction patterns of RuSe2 and RuSe2-T catalysts prepared in Comparative Examples 1 and 2, (a) is a comparison diagram of Examples 1 to 4 and Comparative Example 1, and (b) is a comparison diagram of Example 1 and Comparative Example 2.

[0023] Figure 5 : Ru / RuSe prepared in Example 1 x High-resolution transmission electron microscopy of the -43 catalyst.

[0024] Figure 6 Polarization curves obtained by linear sweep voltammetry (LSV) testing of the catalysts prepared in Example 1 and Comparative Examples 1 and 2, and the commercial catalyst 20% Pt / C in alkaline water and alkaline seawater. Figure (a) is a 1 M KOH aqueous solution, and Figure (b) is a 1 M KOH + real seawater solution.

[0025] Figure 7Figure 1: Overpotential data at different current densities obtained from LSV tests of the catalysts prepared in Examples 1-4 and Comparative Example 1, and the commercial catalyst 20% Pt / C in alkaline water and alkaline seawater. Figure (a) is a 1 M KOH aqueous solution, and Figure (b) is a 1 M KOH + real seawater solution.

[0026] Figure 8 : Electrochemical impedance spectroscopy (EIS) graphs of the catalysts prepared in Example 1 and Comparative Examples 1 and 2, and the commercial catalyst 20% Pt / C under open circuit potential conditions in alkaline water and alkaline seawater. Figure (a) is a 1M KOH aqueous solution, and Figure (b) is 1M KOH + real seawater.

[0027] Figure 9 The catalyst prepared in Example 1 was assembled into an anion exchange membrane flow electrolyzer and subjected to 800 mA·cm -2 Long-term stability test curve under current density. DETAILED DESCRIPTION

[0028] The following examples further illustrate the specific implementation of the present invention, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are any processes not specifically described below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0029] Example 1 Heterostructured electrocatalyst Ru / RuSe x Preparation: (1) Preparation of RuSe2 precursor powder ① Disperse 2.62 mL of 50 mg / mL RuCl3·3H2O in 20 mL of ionized water, add 0.8 mmol of disodium ethylenediaminetetraacetate, and stir for 1 hour to prepare complex solution A. ② Dissolve 1 mmol of Se powder in 5 mL of 20 M KOH aqueous solution to prepare solution B; ③ Complex solution A was slowly added dropwise to solution B and mixed evenly, then transferred to a high-pressure reactor and placed in an oven at 180°C for hydrothermal reaction for 24 hours; after naturally cooling to room temperature, the mixture was centrifuged and washed until the pH of the supernatant was neutral, and then dried to obtain RuSe2 powder; (2) Joule heating treatment ① The RuSe2 powder is evenly dispersed on the conductive carbon paper. The two ends of the carbon paper are fixed on the electrodes of the Joule heating device, and an argon atmosphere is introduced into the device. ② After heating to 550℃ with a constant current of 43 A and holding for 40 seconds, a heterostructure electrocatalyst containing metallic Ru nanoparticles and selenium vacancies was formed, labeled Ru / RuSe. x -43.

[0030] Example 2 Step (2) ② The constant current is 33 A, and the temperature is heated to 380°C. The remaining steps are the same as those in Example 1, and are marked as Ru / RuSe. x -33.

[0031] Example 3 Step (2) ② The constant current is 38 A, and the temperature is heated to 470 ° C. The remaining steps are the same as those in Example 1, and are marked as Ru / RuSe. x -38.

[0032] Example 4 Step (2) ② The constant current is 48 A, and the temperature is heated to 600 ° C. The remaining steps are the same as in Example 1, and are marked as Ru / RuSe. x -48.

[0033] Example 5 Heterostructured electrocatalyst Ru / RuSe x Preparation: (1) Preparation of RuSe2 precursor powder ① Disperse 1.31 mL of 100 mg / mL RuCl3·3H2O in 20 mL of ionized water, add 1.0 mmol of disodium ethylenediaminetetraacetate, and stir for 0.5 hour to prepare complex solution A. ② Prepare solution B by dissolving 1.5 mmol of Se powder in 7.5 mL of 18 M concentrated KOH aqueous solution; ③ Complex solution A was slowly added dropwise to solution B and mixed evenly, then transferred to a high-pressure reactor and placed in a 140°C oven for hydrothermal reaction for 36 hours. After naturally cooling to room temperature, the mixture was centrifuged and washed until the pH was neutral, and then dried to obtain RuSe2 powder; (2) Joule heating treatment ① The RuSe2 powder is evenly dispersed on the conductive carbon paper. The two ends of the carbon paper are fixed on the electrodes of the Joule heating device, and the device is then introduced into an argon atmosphere containing hydrogen; ② A constant current of 60 A was passed through the solution, and after heating to 550°C, the temperature was maintained for 15 seconds to form a heterostructured electrocatalyst containing metallic Ru nanoparticles and selenium vacancies.

[0034] Example 6 Heterostructured electrocatalyst Ru / RuSe x Preparation: (1) Preparation of RuSe2 precursor powder ① Disperse 0.66 mL of 200 mg / mL RuCl3·3H2O in 20 mL of ionized water, add 0.6 mmol of disodium ethylenediaminetetraacetate, and stir for 2 hours to prepare complex solution A. ② Prepare solution B by dissolving 0.75 mmol of Se powder in 3.75 mL of 15 M concentrated KOH aqueous solution; ③ Complex solution A was slowly added dropwise to solution B and mixed evenly. The mixture was transferred to a high-pressure reactor and placed in an oven at 200°C for hydrothermal reaction for 8 hours. After cooling naturally to room temperature, the mixture was centrifuged and washed until the pH was neutral. Finally, it was dried to obtain RuSe2 powder. (2) Joule heating treatment ① The RuSe2 powder is evenly dispersed on the conductive carbon paper. The two ends of the carbon paper are fixed on the electrodes of the Joule heating device, and a nitrogen atmosphere is introduced into the device. ② A constant current of 25A was passed through the reactor, and the mixture was heated to 380°C and kept at this temperature for 120 seconds to form a heterostructured electrocatalyst containing metallic Ru nanoparticles and selenium vacancies.

[0035] Comparative Example 1 The RuSe2 powder synthesized in step 1 was not subjected to Joule heating treatment, and the remaining steps were the same as those in Example 1 and were labeled as RuSe2.

[0036] Comparative Example 2 Step (1) is the same as in Example (1); (2) Preparation of RuSe2-T powder: ① Weigh 100 mg of RuSe2 powder synthesized in step 1, place it in an alumina porcelain boat, transfer it to a tube furnace, and maintain a temperature of 50 mL min -1 Argon gas was introduced at a rate of 30 min; ② Heat treatment was performed under argon atmosphere. The specific heating rate was set at 5 ℃·min -1 , heating from room temperature to 550 ℃, keeping warm for 2 hours and then naturally cooling to room temperature to obtain the heat-treated RuSe2 sample, marked as RuSe2-T.

[0037] Experimental Example 1 Catalyst Characterization Test 1. Prepare the Ru / RuSe prepared in Example 1 x The catalyst was tested by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0038] (1) By Figure 1 It can be seen that the Ru / RuSe prepared in Example 1 x The SEM image of the -43 catalyst showed a well-dispersed, nearly spherical nanoparticle structure with an average size of 52.8 nm.

[0039] (2) By Figure 2 It can be seen that the Ru / RuSe prepared in Example 1 x TEM images of the -43 catalyst show that ultra-small Ru metal nanoparticles are uniformly distributed and stably anchored on the RuSe2 surface. Image processing and statistical analysis show that the average particle size of the Ru nanoparticles is approximately 4.0 nm.

[0040] 2. Prepare the Ru / RuSe prepared in Example 1 x Electron paramagnetic resonance (EPR) tests were performed on the RuSe2 prepared by -43 catalyst and Comparative Example 1.

[0041] Depend on Figure 3 It can be seen that the Ru / RuSe prepared in Example 1 x The EPR spectrum of the -43 catalyst shows a strong selenium vacancy signal at g=2.003, which is in sharp contrast to the comparative example 1 with no vacancy signal.

[0042] 3. Prepare the Ru / RuSe obtained in Example 1-4 x -33.Ru / RuSe x -38、Ru / RuSe x -43.Ru / RuSe x X-ray diffraction (XRD) tests were performed on the RuSe2-48 catalyst and the RuSe2 and RuSe2-T catalysts prepared in Comparative Examples 1 and 2.

[0043] Depend on Figure 4 (a) It can be seen that the XRD spectrum of RuSe2 prepared in Comparative Example 1 shows that its crystallinity is low, and there are two weak and broad characteristic peaks at 30° and 55°, which is consistent with the hexagonal structure of transition metal dichalcogenides; the Ru / RuSe prepared in Examples 1 to 4 x -33.Ru / RuSe x -38、Ru / RuSe x -43.Ru / RuSe x The XRD spectrum of the -48 catalyst shows that the catalyst has characteristic diffraction peaks of cubic phase RuSe2 and high crystallinity, and also has the characteristic peaks of the (101) crystal plane of hexagonal phase metal Ru. Figure 4 (b) It can be seen that comparative example 2 only has the characteristic diffraction peak of cubic phase RuSe2.

[0044] 4. Prepare the Ru / RuSe prepared in Example 1 x The catalyst was tested by high-resolution transmission electron microscopy (HRTEM).

[0045] Figure 5 The HRTEM image shows that the lattice fringe spacing of the nanoparticles is 0.234 nm and 0.205 nm, corresponding to the (100) and (101) crystal planes of hexagonal close-packed ruthenium metal, respectively; in addition, the lattice fringe spacing of the (311) crystal plane belonging to the cubic phase RuSe2 is also observed, which is 0.178 nm.

[0046] Experimental Example 2 Electrochemical Performance Test 1. Electrode Material Preparation The catalysts prepared in Example 1 and Comparative Examples 1 and 2, as well as a commercial catalyst 20% Pt / C, were dispersed in a mixed solvent containing 950 μL of ethanol and 50 μL of perfluorosulfonic acid resin, followed by ultrasonic treatment for 30 minutes to prepare a slurry. The resulting slurry was sprayed onto a carbon paper substrate using an air spray gun on a hot plate. The catalyst loading was 1.0 mg cm -2 .

[0047] 2. Test Method Electrochemical performance tests were performed in a three-electrode system with a Hg / HgO electrode as the reference electrode, a graphite rod electrode as the counter electrode, carbon paper sprayed with the catalyst as the working electrode, and a 1 M KOH aqueous solution or seawater solution as the electrolyte. The potential was referenced to the reversible hydrogen electrode (RHE): E RHE = E Hg / HgO +0.098+0.0592×pH. The overpotential (η) is calculated according to the following equation: η= E RHE Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV / s to obtain polarization curves. All LSV polarization curves were compensated for 95% of the resistance voltage drop. Electron transport properties were determined by electrochemical impedance spectroscopy (EEIS) at open circuit potential in alkaline water and alkaline seawater solutions.

[0048] 3. Test Results Depend on Figure 6 (a) and (b) Linear sweep voltammetry (LSV) test graphs show that compared with the catalysts prepared in Comparative Examples 1 and 2 of the present invention and the commercial catalyst 20% Pt / C, the Ru / RuSe prepared in Example 1 x-43 catalyst has better performance in alkaline water and alkaline seawater; the polarization current of the RuSe2 catalyst prepared in comparative example 1 is the lowest. After Joule heating treatment, the polarization current density is significantly improved, and the hydrogen evolution activity is significantly improved. Compared with the RuSe2-T catalyst heated in a tube furnace, the Ru / RuSe x -43 catalyst has better hydrogen evolution catalytic activity.

[0049] Depend on Figure 7 (a) It can be seen that Ru / RuSe x -43 catalyst at 10 mA·cm -2 、100 mA·cm -2 and 200 mA·cm -2 At the current density, the overpotential is as low as 21 mV, 78 mV and 115 mV, respectively, which is significantly lower than that of RuSe2 prepared in Comparative Example 1 (55 mV, 165 mV, 224 mV) and the commercial 20% Pt / C catalyst (25 mV, 129 mV, 190 mV).

[0050] Depend on Figure 7 (b) shows Ru / RuSe x -43 catalyst at 10 mA·cm -2 、100 mA·cm -2 and 200 mA·cm -2 The overpotentials at the current density were 26 mV, 101 mV, and 150 mV, respectively, which were significantly lower than those of the RuSe2 prepared in Comparative Example 1 and the commercial 20% Pt / C catalyst.

[0051] Depend on Figure 8 It can be seen that the Ru / RuSe prepared in Example 1 x Compared with the catalysts prepared in Comparative Examples 1 and 2 and the commercial catalyst 20% Pt / C, the -43 catalyst has a smaller AC impedance under open circuit potential conditions in alkaline water and alkaline seawater.

[0052] Table 1 shows the comparison of hydrogen evolution activity of other ruthenium-based or selenium-based electrocatalysts and the catalyst of the present invention in 1M KOH and alkaline seawater. x -43 overpotentials are 21 mV and 26 mV, respectively, which are lower than those of other catalysts. x The hydrogen evolution activity is better than that of other ruthenium-based or selenium-based electrocatalysts reported previously.

[0053] Table 1 Comparison of hydrogen evolution activity of other ruthenium-based or selenium-based electrocatalysts and the catalyst of the present invention in 1 M KOH and alkaline seawater

[0054] [1] J. Sun, X. Meng, Z. Zhang, Z. Li, Interface-induced phase engineering to boost intrinsic catalytic activity of nickel selenide for improved water / seawater hydrogen evolution, Journal of Alloys and Compounds 967 (2023) 171815. [2] H. Huang, H. Jung, C.-Y. Park, S. Kim, A. Lee, H. Jun, J. Choi, JW Han, J. Lee, Surface conversion derived core-shell nanostructures of Coparticles@RuCo alloy for superior hydrogen evolution in alkali and seawater, AppliedCatalysis B: Environmental 315 (2022) 121554. [3] S. Wang, M. Wang, Z. Liu, S. Liu, Y. Chen, M. Li, H. Zhang, Q.Wu, J. Guo, X. Feng, Z. Chen, Y. Pan, Synergetic function of the single-atomRu–N4site and Ru nanoparticles for hydrogen production in a wide pH range andseawater electrolysis, ACS Applied Materials&Interfaces 14(13) (2022) 15250-15258. [4] J. Li, R. Guo, X. Zang, Y. Wang, H. Li, W. Xiao, L. Xin, Y. Zong,G. Fu, Z. Wu, L. Wang, Surficial-enriched Ru on octahedral CeO2with strongelectronic interactions as an efficient electrocatalyst for hydrogen generation in alkaline freshwater / seawater, Inorganic Chemistry Frontiers 12(2)(2025) 821-832. [5] J. Sun, Z. Zhao, Z. Li, Z. Zhang, R. Zhang, X. Meng, Ultrafast carbothermal shocking fabrication of cation vacancy-rich Mo doped Runanoparticles on carbon nanotubes for high-performance water / seawater electrolysis, Journal of Materials Chemistry A 11(41) (2023) 22430-22440. [6] J. Zhu, R. Lu, W. Shi, L. Gong, D. Chen, P. Wang, L. Chen, J. Wu,S. Mu, Y. Zhao, Epitaxially grown Ru clusters–nickel nitride heterostructure advances water electrolysis kinetics in alkaline and seawater media, Energy&EnvironmentalMaterials 6(2) (2022) e12318. [7] B. Jiang, Z. Wang, H. Zhao, X. Wang, X. Mao, A. Huang, X. Zhou, K. Yin, K. Sheng, J. Wang, Ru nanoclusters anchored on boron- and nitrogen-doped carbon for a highly efficient hydrogen evolution reaction in alkaline seawater, Nanoscale 15(48) (2023) 19703-19708. [8] R. Andaveh, A. Sabour Rouhaghdam, J. Ai, M. Maleki, K. Wang, A.Seif, G. Barati Darband, J. Li, Boosting the electrocatalytic activity of NiSe by introducing MnCo as an efficient heterostructured electrocatalyst for large-current-density alkaline seawater splitting, Applied Catalysis B:Environmental 325 (2023) 122355. Experimental Example 3 Anion Exchange Membrane Electrolyzer Test 1. Test Method The catalyst was further assembled into a membrane electrode, with Example 1 as the cathode and a homemade nickel foam self-supporting layered nickel-iron double hydroxide as the anode, assembled on both sides of the anion exchange membrane to form a complete electrolytic cell, and an anion exchange membrane water electrolyzer test was carried out.

[0055] 2. Test Results Depend on Figure 9 It can be seen that the system exhibits excellent long-term stability in alkaline seawater environment, with a current density of 800 mA·cm -2 The required applied voltage was 2.08 V, and the electrolyzer voltage hardly increased after 400 hours of continuous operation at constant current. Stable hydrogen evolution reaction at industrial-grade current density was achieved under alkaline seawater conditions.

[0056] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A vacancy-rich Ru / RuSe x Heterostructure electrocatalyst, characterized in that The electrocatalyst is composed of a cubic RuSe2 matrix rich in selenium vacancies and metal Ru nanoparticles uniformly distributed and stably anchored on the surface of RuSe2; the cubic RuSe2 matrix rich in selenium vacancies belongs to Pa3 - The invention discloses a cubic crystal system of a space group, wherein Ru atoms are located in a face-centered cubic lattice, and Se atoms form Se2 pairs and fill the octahedral interstitial sites in the crystal system to form a stable Ru-Se coordination structure; the selenium vacancies exhibit a three-dimensional uniform distribution characteristic in the matrix and are preferentially enriched along high-energy crystal planes; a clear heterogeneous interface exists between the metal Ru nanoparticles anchored on the RuSe2 surface and the matrix, and the particles are tightly anchored by bonding.

2. The vacancy-rich Ru / RuSe according to claim 1 x Heterostructure electrocatalyst, characterized in that The average size of the catalyst is 30-80 nm, and the average size of the metal Ru nanoparticles is 2-8 nm.

3. A vacancy-rich Ru / RuSe according to claim 1 or 2 x A method for preparing a heterostructure electrocatalyst, characterized in that: The method comprises the following steps: The precursor RuSe2 powder is synthesized by hydrothermal method, and then the RuSe2 powder is subjected to Joule heating in an inert atmosphere or a reducing atmosphere to obtain vacancy-rich Ru / RuSe x Heterostructured electrocatalysts.

4. The preparation method according to claim 3, characterized in that The hydrothermal method for synthesizing the precursor RuSe2 powder specifically comprises the following steps: (1) Disperse RuCl3·3H2O in deionized water, add disodium ethylenediaminetetraacetic acid and stir for 0.5-2 hours to prepare complex solution A; (2) Dissolve Se powder in concentrated KOH aqueous solution to prepare solution B; (3) Complex solution A is slowly added dropwise to solution B and mixed evenly, then transferred to a high-pressure reactor for hydrothermal reaction at 140-200°C for 8-36 hours. After cooling, the mixture is centrifuged until the pH is neutral and dried to obtain RuSe2 powder.

5. The preparation method according to claim 3, characterized in that The inert atmosphere is one of argon, nitrogen, and helium, and the reducing atmosphere is one of argon containing hydrogen, nitrogen containing hydrogen, and helium containing hydrogen.

6. The preparation method according to claim 3, characterized in that The Joule heating is performed using a constant current of 25 to 60 A, a heating temperature of 380 to 600° C., and maintained for 15 to 120 seconds.

7. The preparation method according to claim 6, characterized in that The Joule heating is preferably performed using a constant current of 43A to 48A, and the heating temperature is preferably 550 to 600°C.

8. The preparation method according to claim 4, characterized in that The molar ratio of RuCl3·3H2O, disodium ethylenediaminetetraacetate, and Se is 1:(1.2-2):(1.5-3).

9. The preparation method according to claim 4, characterized in that The concentration of RuCl3·3H2O is 0.05-0.3 g / mL, and the concentration of KOH is 15-20 M.

10. The vacancy-rich Ru / RuSe according to claim 1 or 2 x Application of heterostructure electrocatalysts, characterized in that The catalyst is used for electrolyzing seawater to produce hydrogen.

Citation Information

Patent Citations

  • Selenium vacancy molybdenum selenide material, preparation thereof and application of selenium vacancy molybdenum selenide material in HER catalysis

    CN116002633A

  • Transition metal selenide / noble metal selenide heterostructure hydrogen evolution reaction electrocatalyst and preparation method and application thereof

    CN118773657A

  • Preparation method of transition metal selenide electrocatalyst rich in selenium defect and water electrolysis application of transition metal selenide electrocatalyst

    CN118792682A

  • Marine antifouling coating with active-passive synergistic mechanism and preparation method thereof

    CN120098544A

  • APPARATUS AND METHOD FOR TRAINING NeRF MODEL

    KR102793927B1

Cited By

  • Method for stable electrolytic hydrogen production of high-salt water body based on assistance of ferrous cyanide cyclic regeneration

    CN121295202A